Nauczanie języków obcych uczniów z zespołem Aspergera - Kolera, Małgorzata (Neofilolog, 2011)
The paper presents an overview of issues pertaining to teaching foreign languages to pupils with Asperger syndrome at school. Following a brief background to the impairments, it proceeds to discuss the significance of learning foreign languages by pupils with Asperger syndrome as it can lead to beneficial effects on their overall development. The article also analyses the profile of attitudes, knowledge and skills of foreign language teachers working with Asperger syndrome learners. The paper finishes with an attempt to depict the main difficulties that Asperger syndrome pupils and their teachers face during foreign language classes and to present strategies for intervention.